Positive electrode current collector with solid electrolyte surface treatment and preparation method and application thereof

Through solid electrolyte surface treatment and the use of nano-scale carbon materials, the problems of high impedance, insufficient cycle performance and strong temperature rise effect of lithium-ion batteries are solved, and batteries with low impedance, high cycle performance and weak temperature rise effect are achieved. performance.

CN115458747BActive Publication Date: 2025-02-18HUZHOU NANMU-NANO SCI & TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211329892.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-27
Publication Date
2025-02-18
Estimated Expiration
2042-10-27

AI Technical Summary

Technical Problem

The current lithium-ion battery positive electrode current collector has a high impedance, insufficient circulation performance, and strong temperature rise effect, resulting in less significant improvement in the performance of the power battery.

Method used

The positive electrode current collector preparation method is adopted with solid electrolyte surface treatment. The conductivity of the aluminum foil coating layer is increased through nano-scale carbon materials, and the interface between the positive electrode current collector and the electrolyte is regulated through solid electrolyte to reduce the interface impedance.

Benefits of technology

Effectively reduce battery impedance, improve long cycle performance, weaken temperature rise effect, and excellent overall electrical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115458747B_ABST
    Figure CN115458747B_ABST
Patent Text Reader

Abstract

The embodiment of the present invention relates to a positive electrode current collector with solid electrolyte surface treatment, a preparation method and an application. The preparation method comprises: by weight, 40-75 parts of water and 0.1-0.5 parts of thickener are mixed and dispersed at high speed for 20-60 minutes, then 20-40 parts of solid electrolyte are added and dispersed at high speed for 30-90 minutes, and then 0.1-0.5 parts of wetting agent are added and dispersed at high speed for 20-60 minutes to obtain a first slurry; by weight, 1-3 parts of dispersant, 50-90 parts of water, and 0-20 parts of solvent are mixed and dispersed at high speed until uniform, and then 5-20 parts of nano-scale carbon material are added, The second slurry is obtained by high-speed dispersion for 2-5 hours; 3-10 parts of the first slurry and 75-90 parts of the second slurry are mixed at high speed by weight, 0.5-1.5 parts of a pH adjuster and 0.1-0.5 parts of a leveling agent are added and mixed evenly at a low speed, and finally 4-10 parts of a binder are added to obtain a conductive slurry of a positive electrode current collector with a solid electrolyte surface treatment; the conductive slurry is evenly coated on the surface of the aluminum foil to obtain a positive electrode current collector with a solid electrolyte surface treatment for a power battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new energy materials, and in particular to a positive electrode current collector with solid electrolyte surface treatment, a preparation method and an application thereof. Background Art

[0002] Lithium-ion batteries have been developed since the 1960s and have become mature commercial batteries. They have almost completely replaced traditional secondary batteries. The reason is that lithium-ion batteries have advantages that traditional batteries cannot match: higher output voltage than traditional secondary batteries, higher energy density than traditional batteries, longer service life than traditional batteries, environmental protection, less pollution, smaller memory effect, and better storage performance than other batteries. Since the development of lithium-ion batteries, they have been rapidly updated and have a very broad prospect, but there are still some problems that need to be solved. Power lithium-ion batteries are not safe, easy to catch fire and explode, and have unreliable safety performance; people's growing needs and continuous innovation in science and technology have led to higher requirements for lithium ions. Breakthroughs in cycle performance and improvements in rate performance are all directions that lithium-ion batteries need to develop. The main materials of lithium batteries include positive electrode materials, negative electrode materials, electrolytes and diaphragms. However, in addition to the four main parts, the current collector used to store positive and negative electrode materials is also an important part of lithium batteries. For lithium-ion batteries, the commonly used positive current collector is aluminum foil and the negative current collector is copper foil.

[0003] In the field of lithium batteries, aluminum foil is used as the current collector of lithium-ion batteries. Usually, the lithium-ion battery industry uses rolled aluminum foil as the positive electrode collector. The current collector plays an important role in improving the charging and discharging efficiency of lithium batteries. By coating the surface of aluminum foil with conductive slurry, the polarization of the battery can be suppressed, the thermal effect can be reduced, and the rate performance of the battery can be improved. At the same time, the adhesion between the active material and the aluminum foil can be improved, and the amount of binder can be reduced.

[0004] To solve the above problems, patent CN 104538638 B discloses a lithium ion battery positive electrode aluminum foil conductive agent and a preparation method thereof, which is prepared from the following raw materials in weight percentage: graphite 15.0%-22.0%, conductive carbon black 3.0%-6.0%, modified water-based epoxy resin 5.0%-10.0%, butadiene styrene polymer 11.0%-25.0%, sodium carboxymethyl cellulose 0.1%-1.5%, sodium polyacrylate 0.05%-0.5%, peach gum 2.0%-6.5%, 2-amino-2-methyl-1-propanol 0.3%-0.8%, polyoxyethylene sorbitan monolaurate 0.05%-0.5%, polyvinyl pyrrolidone 0.2%-0.7%, sodium methylene bis naphthalene sulfonate 0.3%-1.0%, ammonia water 2.0%-6.0%, and the balance is deionized water. This invention provides a lithium-ion battery positive electrode aluminum foil conductive agent with good conductivity, good adhesion and good solvent tolerance. However, the carbon-coated aluminum foil has a high impedance, a high temperature rise effect after being made into a battery, no obvious increase in cycle performance, and no significant improvement in power battery performance.

[0005] In summary, the development of a conductive slurry with low impedance, good long cycle performance and weak temperature rise effect has broad market application value and prospects, and can effectively promote the further development of the lithium battery industry. Summary of the invention

[0006] The purpose of the present invention is to provide a positive electrode current collector with solid electrolyte surface treatment and a preparation method and application, which can reduce battery impedance, increase battery long cycle, and improve the temperature rise effect of the battery.

[0007] To this end, in a first aspect, an embodiment of the present invention provides a method for preparing a positive electrode current collector having a solid electrolyte surface treatment, the preparation method comprising:

[0008] Calculated by weight, 40-75 parts of water and 0.1-0.5 parts of thickener are mixed, dispersed at high speed for 20-60 minutes, and then 20-40 parts of solid electrolyte are added, dispersed at high speed for 30-90 minutes, and then 0.1-0.5 parts of wetting agent are added, and dispersed at high speed for 20-60 minutes to obtain a first slurry;

[0009] Calculated by weight, 1-3 parts of dispersant, 50-90 parts of water, and 0-20 parts of solvent are mixed and dispersed at high speed until uniform, and then 5-20 parts of nano-scale carbon material are added and dispersed at high speed for 2-5 hours to obtain a second slurry;

[0010] Calculated by weight, 3-10 parts of the first slurry and 75-90 parts of the second slurry are mixed at high speed, and then 0.5-1.5 parts of a pH adjuster and 0.1-0.5 parts of a leveling agent are added and mixed evenly at a low speed, and finally 4-10 parts of a binder are added to obtain a conductive slurry of a positive electrode current collector with a solid electrolyte surface treatment;

[0011] The conductive slurry is evenly coated on the surface of the aluminum foil to obtain a positive electrode current collector with solid electrolyte surface treatment for a power battery.

[0012] Preferably, the equipment used for the high-speed dispersion includes: one or more of a high-speed disperser, a high-speed shear emulsifier, a vacuum degassing disperser, and a sand mill; the dispersion speed of the high-speed dispersion is 2000r / min-12000r / min; the dispersion speed of the low-speed dispersion is 200r / min-500r / min.

[0013] Preferably, the thickener includes: one or more of methyl cellulose, hydroxyethyl cellulose, modified starch, polyvinyl alcohol, polyethylene wax, and polymethacrylate;

[0014] The wetting agent includes: one or more of sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, polyethylene glycol and alkylphenol polyoxyethylene ether;

[0015] The solid electrolyte comprises: a mixture of one or more of a garnet-type solid electrolyte material, a NASICON-type solid electrolyte material, a LISICON-type solid electrolyte material, and a perovskite-type solid electrolyte material;

[0016] The nano-scale carbon material comprises: a mixture of one or more of carbon black, graphene and carbon nanotubes; wherein the carbon black has a primary particle size D50 of 30nm-60nm, the graphene is a single-layer graphene or a multi-layer graphene, and the carbon nanotube is a single-walled carbon nanotube or a multi-walled carbon nanotube;

[0017] The solvent comprises: a mixture of one or more of ethylene glycol, propylene glycol, hexylene glycol, ethylene glycol butyl ether, propylene glycol methyl ether, propylene glycol ethyl ether, propylene glycol butyl ether, dipropylene glycol monomethyl ether, dipropylene glycol monopropyl ether, dipropylene glycol monobutyl ether, tripropylene glycol n-butyl ether, propylene glycol phenyl ether, hexylene glycol butyl ether acetate, and 3-ethoxyethyl propionate;

[0018] The dispersant is a hydrophilic acrylic acid hyperbranched block copolymer;

[0019] The pH regulator comprises: a mixture of one or more of ammonia water, 2-amino-2-methyl-1-propanol, dimethylethanolamine, N-methylethanolamine, diethanolamine, butylethanolamine, 2-amino-2-ethyl-1,3-propanediol, sodium hydroxide, and potassium hydroxide;

[0020] The leveling agent comprises: a mixture of one or more of water-based modified polyacrylate, anionic acrylic copolymer, nonionic polyamine-ethylene oxide condensate, nonionic polyethylene glycol ester, and alkylphenol polyoxyethylene ether;

[0021] The binder includes a mixture of one or more of a polyacrylate binder, a styrene-butadiene rubber (SBR) binder, a polyacrylonitrile binder or other resin binders.

[0022] Preferably, the coating method is one of gravure coating, micro-concave coating, and slit extrusion coating.

[0023] In a second aspect, an embodiment of the present invention provides a positive electrode current collector with a solid electrolyte surface treatment for a power battery, which is prepared by the preparation method described in the first aspect.

[0024] Preferably, the positive electrode current collector comprises: a conductive coating doped with a solid electrolyte and an aluminum foil;

[0025] The conductive slurry for forming the conductive coating doped with the solid electrolyte comprises: a solid electrolyte, a dispersant, a thickener, a wetting agent, water, a second solvent, a nano-scale carbon material, a leveling agent, a pH regulator and a binder.

[0026] In a third aspect, an embodiment of the present invention provides a lithium battery positive electrode comprising the positive electrode current collector for a power battery with a solid electrolyte surface treatment as described in the second aspect above.

[0027] In a fourth aspect, an embodiment of the present invention provides a lithium battery comprising the lithium battery positive electrode described in the third aspect above.

[0028] The preparation method of the positive electrode current collector with solid electrolyte surface treatment provided by the embodiment of the present invention increases the conductivity of the aluminum foil carbon coating layer by nano-scale carbon materials, and effectively regulates the interface between the positive electrode current collector and the electrolyte by adding solid electrolytes. At the same time, because the solid electrolyte itself has relatively high ionic conductivity and electronic insulation performance, it also has a positive significance for reducing the interface impedance. After doping with the solid electrolyte, a stable interface is formed on the surface of the positive electrode current collector, and the continuous reaction with the electrolyte is suppressed. Therefore, the impedance of the battery is stabilized in a long cycle. Therefore, the conductive slurry of the positive electrode current collector aluminum foil doped with a solid electrolyte can effectively improve the performance of the overall lithium battery, including but not limited to reducing impedance, improving the long cycle stability of the battery, and reducing the temperature rise effect of the power battery. . The lithium battery made using the surface-treated positive electrode current collector aluminum foil has low impedance, good long cycle performance, weak temperature rise effect, and excellent overall electrical performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1This is a flow chart of a preparation method for a positive electrode current collector with solid electrolyte surface treatment proposed in an embodiment of the present invention. DETAILED DESCRIPTION

[0030] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments.

[0031] The present invention provides a method for preparing a positive electrode current collector with a solid electrolyte surface treatment, such as Figure 1 As shown, the main steps include:

[0032] Step 110, by weight, 40-75 parts of water and 0.1-0.5 parts of thickener are mixed, dispersed at high speed for 20-60 minutes, then 20-40 parts of solid electrolyte are added, dispersed at high speed for 30-90 minutes, then 0.1-0.5 parts of wetting agent are added, dispersed at high speed for 20-60 minutes, to obtain a first slurry;

[0033] The equipment used for high-speed dispersion includes: one or more of a high-speed disperser, a high-speed shear emulsifier, a vacuum degassing disperser, and a sand mill; the dispersion speed of the high-speed dispersion is 2000r / min-12000r / min.

[0034] The thickener includes: one or more of methyl cellulose, hydroxyethyl cellulose, modified starch, polyvinyl alcohol, polyethylene wax, and polymethacrylate;

[0035] The wetting agent includes: one or more of sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, polyethylene glycol and alkylphenol polyoxyethylene ether;

[0036] The solid electrolyte includes: a mixture of one or more of garnet-type solid electrolyte materials, NASICON-type solid electrolyte materials, LISICON-type solid electrolyte materials, and perovskite-type solid electrolyte materials.

[0037] Step 120, by weight, 1-3 parts of a dispersant, 50-90 parts of water, and 0-20 parts of a solvent are mixed and dispersed at high speed until uniform, and then 5-20 parts of a nano-scale carbon material are added, and the mixture is dispersed at high speed for 2-5 hours to obtain a second slurry;

[0038] Among them, the dispersion speed of high-speed dispersion is 2000r / min-12000r / min;

[0039] The nano-scale carbon material includes: a mixture of one or more of carbon black, graphene and carbon nanotubes; wherein the primary particle size D50 of the carbon black is 30nm-60nm, the graphene is single-layer graphene or multi-layer graphene, and the carbon nanotube is single-walled carbon nanotube or multi-walled carbon nanotube;

[0040] The solvent includes: a mixture of one or more of ethylene glycol, propylene glycol, hexylene glycol, ethylene glycol butyl ether, propylene glycol methyl ether, propylene glycol ethyl ether, propylene glycol butyl ether, dipropylene glycol monomethyl ether, dipropylene glycol monopropyl ether, dipropylene glycol monobutyl ether, tripropylene glycol n-butyl ether, propylene glycol phenyl ether, hexylene glycol butyl ether acetate, and 3-ethoxyethyl propionate;

[0041] The dispersant is a hydrophilic acrylic acid hyperbranched block copolymer. The block copolymer dispersant can concentrate the anchoring segment during dispersion, enhance the anchoring effect, and complex with the nano-carbon material to obtain an excellent dispersion effect. In addition, the acrylic acid copolymer provides good adhesion of the slurry on the surface of the aluminum foil and increases the stability of the coating.

[0042] Step 130, taking 3-10 parts of the first slurry and 75-90 parts of the second slurry by weight, mixing them at high speed, then adding 0.5-1.5 parts of a pH adjuster and 0.1-0.5 parts of a leveling agent, mixing them at low speed, and finally adding 4-10 parts of a binder to obtain a conductive slurry of a positive electrode current collector with a solid electrolyte surface treatment;

[0043] Among them, the dispersion speed of low-speed dispersion is 200r / min-500r / min.

[0044] The pH regulator includes: a mixture of one or more of ammonia water, 2-amino-2-methyl-1-propanol, dimethylethanolamine, N-methylethanolamine, diethanolamine, butylethanolamine, 2-amino-2-ethyl-1,3-propanediol, sodium hydroxide, and potassium hydroxide;

[0045] The leveling agent includes: a mixture of one or more of water-based modified polyacrylate, anionic acrylic copolymer, nonionic polyamine-ethylene oxide condensate, nonionic polyethylene glycol ester, and alkylphenol polyoxyethylene ether;

[0046] The adhesive includes a mixture of one or more of polyacrylate adhesive, styrene-butadiene rubber (SBR) adhesive, polyacrylonitrile adhesive or other resin adhesives.

[0047] Step 140, evenly coating the conductive slurry on the surface of the aluminum foil to obtain a positive electrode current collector with a solid electrolyte surface treatment for a power battery.

[0048] The coating method is one of gravure coating, micro-concave coating and slit extrusion coating.

[0049] The positive electrode current collector with solid electrolyte surface treatment for power battery prepared by the present invention comprises: a conductive coating doped with solid electrolyte and aluminum foil;

[0050] The conductive slurry for forming the solid electrolyte doped conductive coating includes: solid electrolyte, dispersant, thickener, wetting agent, water, second solvent, nano-scale carbon material, leveling agent, pH adjuster and binder. The specific usable materials of each part of the material have been described above and will not be repeated here.

[0051] The positive electrode current collector can be used as a positive electrode of a lithium battery and applied in a lithium battery.

[0052] The positive electrode current collector with solid electrolyte surface treatment and the preparation method thereof proposed in the present invention are described above. The following is a further detailed description of the positive electrode current collector through some specific embodiments, but the protection scope of the present invention is not limited thereto.

[0053] Example 1

[0054] This example provides a method for preparing a surface-treated positive electrode current collector aluminum foil containing a solid electrolyte for a power battery, comprising the following steps:

[0055] S1: Calculated by weight, 60 parts of water and 0.5 parts of hydroxyethyl cellulose thickener were mixed, dispersed at 8000r / min for 40 minutes, and then 39 parts of solid electrolyte Li7La3Zr2O were added. 12 The mixture was dispersed at the same speed for 45 minutes, and then 0.5 parts of alkylphenol polyoxyethylene ether, a wetting agent and surfactant, was added, and the mixture was dispersed at the same speed for 60 minutes to obtain a first slurry;

[0056] S2: Calculated by weight, 2 parts of a dispersant hydrophilic acrylic hyperbranched block copolymer, 75 parts of water, and 8 parts of ethylene glycol butyl ether were mixed and dispersed at high speed until uniform, and then 15 parts of nano carbon black were added, and the mixture was dispersed at a high speed of 6000 r / min for 4 hours to obtain a second slurry;

[0057] S3: Calculated by weight, 8 parts of the first slurry and 83 parts of the second slurry are mixed at high speed, and then 1 part of the pH regulator dimethylethanolamine is added and mixed at 500r / min, and finally 8 parts of the binder are added to obtain a conductive slurry for a positive electrode current collector with a solid electrolyte surface treatment for a power battery;

[0058] S4: The conductive slurry is extruded and coated by slit, and the dry film thickness is controlled at 1um, and is evenly coated on the surface of the aluminum foil, and finally a positive electrode current collector with solid electrolyte surface treatment for a power battery is obtained.

[0059] Example 2

[0060] This example provides a method for preparing a surface-treated positive electrode collector aluminum foil containing a solid electrolyte for a power battery, which is basically the same as Example 1, except that in step S3, 10 parts of the first slurry and 84.5 parts of the second slurry are taken by weight and mixed at high speed in a conventional high-speed disperser, and then 0.5 parts of a pH regulator are added to mix well, and finally 5 parts of a binder are added to obtain a surface-treated positive electrode collector aluminum foil conductive slurry containing a solid electrolyte for a power battery.

[0061] Comparative Example 1

[0062] This example provides a method for preparing a surface-treated positive electrode current collector aluminum foil containing a solid electrolyte for a power battery, which is basically the same as Example 1, except that only the second slurry is used to coat the aluminum foil.

[0063] Comparative Example 2

[0064] Take blank aluminum foil as a comparative example.

[0065] The positive electrode current collector aluminum foil of the above embodiments and comparative examples was coated with lithium iron phosphate positive electrode slurry, and a lithium sheet was used as the negative electrode to make a CR2032 button battery. The charging current was 1mA, the charging cut-off voltage was ≥4.3v, and the discharge cut-off voltage was ≤2.5V. The impedance after different cycles at a rate of 0.2C was tested and compared with the blank control aluminum foil to obtain Table 1.

[0066]

[0067] Table 1

[0068] The positive electrode current collector aluminum foils obtained in the above Examples 1, 2 and Comparative Example 1 and blank aluminum foils were made into button batteries and tested according to conventional standards. The cycle retention rates after 1000 cycles at a 1C rate were compared and obtained in Table 2.

[0069] Capacity retention rate Example 1 87.81% Example 2 91.35% Comparative Example 1 75.22% Comparative Example 2 65.53%

[0070] Table 2 measures the equivalent specific heat capacity of the above button cells and compares it with the blank control aluminum foil to obtain Table 3.

[0071] Equivalent specific heat capacity (J / (kg·℃·Ah)) Example 1 57.21 Example 2 60.65 Comparative Example 1 45.16 Comparative Example 2 35.67

[0072] Table 3

[0073] As can be seen from Table 1, the chemical impedance after different cycles at the same rate, the initial impedance of Examples 1 and 2 is almost the same as that of Comparative Example 1, indicating that coating the surface of the current collector with a conductive slurry helps to reduce the initial impedance of the button cell. As the number of cycles increases, the impedance performance of the battery made using the positive current collector prepared by the present invention is better, and as the amount of solid electrolyte added increases, the impedance stability is better, showing better battery performance.

[0074] It can be seen from Table 2 that the coulombic efficiency of the battery made of the positive electrode current collector prepared by the preparation method provided by the embodiment of the present invention is significantly improved, and the cycle retention rate after 1000 cycles at a rate of 1C is significantly improved compared with the control example, especially without adding the solid electrolyte group.

[0075] The higher the specific heat capacity of a material, the better the temperature stability. As can be seen from Table 3, the battery made using the positive electrode current collector prepared by the present invention has a better equivalent specific heat capacity. From another aspect, it shows that it has better temperature stability, which is of great significance to the safety performance of the lithium battery.

[0076] In summary, the preparation method of the positive electrode current collector with solid electrolyte surface treatment provided by the present invention is simple, the equipment and conditions used are easy to obtain, the preparation efficiency is high, and it is suitable for expanding mass production. The lithium battery made of the surface-treated positive electrode current collector aluminum foil has low impedance, good long cycle performance, weak temperature rise effect, and excellent overall electrical performance. It has positive practical significance for the development of lithium batteries.

[0077] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a positive electrode current collector having a solid electrolyte surface treatment, characterized in that: The preparation method comprises: Calculated by weight, 40-75 parts of water and 0.1-0.5 parts of thickener are mixed, dispersed at high speed for 20-60 minutes, and then 20-40 parts of solid electrolyte are added, dispersed at high speed for 30-90 minutes, and then 0.1-0.5 parts of wetting agent are added, and dispersed at high speed for 20-60 minutes to obtain a first slurry; Calculated by weight, 1-3 parts of a dispersant, 50-90 parts of water, and 0-20 parts of a second solvent are mixed and dispersed at high speed until uniform, and then 5-20 parts of a nano-scale carbon material are added and dispersed at high speed for 2-5 hours to obtain a second slurry; Calculated by weight, 3-10 parts of the first slurry and 75-90 parts of the second slurry are mixed at high speed, and then 0.5-1.5 parts of the pH adjuster are added and dispersed evenly at low speed, and finally 4-10 parts of the binder are added to obtain a conductive slurry of a positive electrode current collector with a solid electrolyte surface treatment; The conductive slurry is evenly coated on the surface of the aluminum foil to obtain a positive electrode current collector with solid electrolyte surface treatment for a power battery.

2. The preparation method according to claim 1, characterized in that: The equipment used for the high-speed dispersion includes: one or more of a high-speed disperser, a high-speed shear emulsifier, a vacuum degassing disperser, and a sand mill; the dispersion speed of the high-speed dispersion is 2000r / min-12000r / min; the dispersion speed of the low-speed dispersion is 200r / min-500r / min.

3. The preparation method according to claim 1, characterized in that: The thickener includes: one or more of methyl cellulose, hydroxyethyl cellulose, modified starch, polyvinyl alcohol, polyethylene wax, and polymethacrylate; The wetting agent includes: one or more of sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, polyethylene glycol and alkylphenol polyoxyethylene ether; The solid electrolyte comprises: a mixture of one or more of a garnet-type solid electrolyte material, a NASICON-type solid electrolyte material, a LISICON-type solid electrolyte material, and a perovskite-type solid electrolyte material; The nano-scale carbon material comprises: a mixture of one or more of carbon black, graphene and carbon nanotubes; wherein the carbon black has a primary particle size D50 of 30nm-60nm, the graphene is a single-layer graphene or a multi-layer graphene, and the carbon nanotube is a single-walled carbon nanotube or a multi-walled carbon nanotube; The second solvent comprises: a mixture of one or more of ethylene glycol, propylene glycol, hexylene glycol, ethylene glycol butyl ether, propylene glycol methyl ether, propylene glycol ethyl ether, propylene glycol butyl ether, dipropylene glycol monomethyl ether, dipropylene glycol monopropyl ether, dipropylene glycol monobutyl ether, tripropylene glycol n-butyl ether, propylene glycol phenyl ether, hexylene glycol butyl ether acetate, and 3-ethoxyethyl propionate; The dispersant is a hydrophilic acrylic acid hyperbranched block copolymer; The pH regulator comprises: a mixture of one or more of ammonia water, 2-amino-2-methyl-1-propanol, dimethylethanolamine, N-methylethanolamine, diethanolamine, butylethanolamine, 2-amino-2-ethyl-1,3-propanediol, sodium hydroxide, and potassium hydroxide; The binder includes a mixture of one or more of a polyacrylate binder, a styrene-butadiene rubber (SBR) binder, a polyacrylonitrile binder or other resin binders.

4. The preparation method according to claim 1, characterized in that: The coating method is one of gravure coating, micro-gravure coating and slit extrusion coating.

5. A positive electrode current collector with solid electrolyte surface treatment for a power battery prepared by the preparation method according to any one of claims 1 to 4.

6. The positive electrode current collector with solid electrolyte surface treatment for power battery according to claim 5, characterized in that: The positive electrode current collector comprises: a conductive coating doped with a solid electrolyte and an aluminum foil; The conductive slurry for forming the conductive coating doped with the solid electrolyte comprises: a solid electrolyte, a dispersant, a thickener, a wetting agent, water, a second solvent, a nano-scale carbon material, a pH regulator and a binder.

7. A lithium battery positive electrode comprising the positive electrode current collector for power batteries with a solid electrolyte surface treatment as described in claim 5 or 6.

8. A lithium battery comprising the lithium battery positive electrode as claimed in claim 7.

Citation Information

Patent Citations

  • Lithium-ion battery cathode aluminum foil conductive agent and its preparation method

    CN104538638B

  • Lithium metal cathode, preparation method thereof, and preparation method of all-solid-state battery

    CN110085868A

  • Bipolar lithium ion battery and preparation method thereof

    CN112582666A